The Role of FoMO and Hedonism in Shaping Consumptive Behaviors and Religious Adherence Among Sibolga's Muslim Millennials - Batubara, Azraini (Abrahamic Religions: Jurnal Studi Agama-Agama, 2024)
This study aims to uncover the impact of Fear of Missing Out (FoMO) and hedonism on consumptive behavior among Muslim millennials in Sibolga, North Sumatra, and how these behaviors interact with religious and social values within a culturally and religiously significant context. Employing a qualitative phenomenological approach, the research collected data through observations, in-depth interviews, and documentation involving eleven Muslim millennials in Sibolga. The findings reveal that FoMO and hedonism contribute to increased consumption of luxury goods and experiences, driven by the desire to stay connected with global trends and achieve instant gratification, often at the expense of local religious values and traditions. This tension between engaging in modern lifestyles and maintaining cultural and religious identities presents a significant dilemma for the youth. The study suggests that educational and social interventions focused on sustainability values and spiritual awareness are necessary to help the younger generation balance the pressures of hedonism and excessive digital connectivity.